THE EFFECT OF CAPITAL STRUCTURE, INVESTMENT DECISION AND SALES GROWTH ON COMPANY VALUE - Fitriyah, Nayla Rahmi; Aufa, M (PT. Antis International Publisher, 2024)
This study aims to analyze how the influence of capital structure, investment decisions, and sales growth on company value in Consumer Goods Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2021-2023. The research approach used in this research is quantitative research with secondary data in the form of financial statement documentation. The technique of collecting funds with purposive sampling and the data analysis technique used in this research is multiple linear regression analysis which is processed using the SPSS version 25 program. The population in this study are Consumer Goods Sector Manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023. This study realizes the need to focus on all aspects of financial reporting before deciding to invest, not only looking at increasing sales, but also at the level of capital management to produce good operational activities. From an investment perspective, investors need to consider aspects such as capital structure, investment decisions, and sales growth before deciding to invest in a company.